Translating Empire : José Martí, Migrant Latino Subjects, and American Modernities - Lomas, Laura, 1967- (Book collections on Project MUSE., 2008)
By showing how Marti was a migrant Latino writer who wrote on immigration as well as empire, Lomas shows how Marti "translated" for readers across cultures the misguided North American view of itself as head of a hemispheric body it was destined.